The Relationship Between Chinese College Student Offspring's Physical Activity and Father Physical Activity During COVID-19 Pandemic - Feng Zhang; Wei Liu; Lamei Deng; Zhifu Li; Yajun Wang; Bo Jin (Frontiers Media S.A., 2022)
The purpose of this study was to evaluate the relationship between the physical activity of Chinese college students and the physical activity of their parents. This relationship was examined by linear regression. The results showed that (1) the physical activities of China's college students will be refurbished and used for the parents. The offspring of COVID-19's later generation sports population showed that the offspring's physical activity was not broken during the later stage of the epidemic, and the coefficient of promotion (r = 1.515) (p < 0.01) of the offspring's participation in the physical activities was. (2) The increase or decrease of parents' sports population is affected by their children's occupation. Therefore, it shows the dynamic role of individuals and the two-way nature of socialization in the process of socialization. With the transformation from traditional society to modern society, promoting college students' physical activities can increase parents' physical activities and improve the level of social physical activities.